ETNOGRAFI PERMAINAN TRADISIONAL LARI BALOK DI DESA RIDOMANAH - Abidin, Dindin; Budiman, Indra Adi; Lestari, Debi (DEVOSI, 2024)
The purpose of this service is to introduce the traditional sports game of running blocks in elementary schools in Ridomanah Village, Cibarusah District, Bekasi Regency. The implementation of traditional sports is still not carried out evenly in Indonesian education. Currently, amidst the increasing popularity of modern sports, children's interest in traditional sports activities is decreasing. Especially in Ridomanah village. The lack of introduction of this traditional sport to children, resulting in a lack of knowledge of the rules of play and interest in doing traditional sports including traditional sports games running blocks. Starting from this problem, the community service team between lecturers and students of Universitas Islam 45 made a community service program with the theme of ethnography of traditional sports running blocks in Ridomanah Village with a case study of elementary school children. The main target is elementary school level children with ethnographic methods by conducting socialization and training. The results of the implementation of this activity show an interest or tendency to exercise towards the traditional sport of running blocks. This community service activity has a good effect on children to increase knowledge related to traditional running block games.